Using problem formulation to clarify the meaning of weight of evidence and biological relevance in environmental risk assessments for genetically modified crops. Issue 2 (3rd April 2019) - Raybould, Alan; Holt, Karen; Kimber, Ian
ABSTRACT: Weight of evidence and biological relevance are important concepts for risk assessment and decision-making over the use of GM crops; however, their meanings are not well defined. We use problem formulation to clarify the definition of these concepts and thereby identify data that are relevant for risk assessment. Problem formulation defines criteria for the acceptability of risk and devises rigorous tests of the hypothesis that the criteria are met. Corroboration or falsification of such hypotheses characterize risk and enable predictable and transparent decisions about whether certain risks from using a particular GM crop are acceptable. Decisions based on a weight of evidence approach use a synthesis of several lines of evidence, whereas a "definitive" approach to risk assessment enables some decisions to be based on the results of a single test. Data are biologically relevant for risk assessment only if they test a hypothesis that is useful for decision-making.